A hacker's mind : how the powerful bend society's rules, and how to bend them back - Schneier, Bruce, 1963- (W.W. Norton and Company, 2024)
It's not just computers--hacking is everywhere. Legendary cybersecurity expert and New York Times best-selling author Bruce Schneier reveals how using a hacker's mindset can change how you think about your life and the world.